La Arcillosa 2: zooarchaeological record of human ocupation during the middle holocene, Tierra del Fuego Argentina - Salemme, Mónica; Santiago, Fernando; Oria, Jimena (Revista Chilena de Antropología, 2015)
La Arcillosa 2 is a shell midden located along the right margin of the Chico river, two kilometers westwards of the present Atlantic coast. This multicomponent site has been dated between 5500 and 3700 years B.P. The permanent aeolian action has disturbed the site, composed mainly by Mytilus edulis shells. It is composed mainly of mussels and in less proportion of terrestrial and marine vertebrates (camelids, canids, rodents, cetaceans, pinnipeds, fishes and birds); they are associated to a lithic assemblage of different raw material and bone artifacts made on bird long bones, decorated with incisions, and a bony bead.